Gamma-knife radiosurgery in the treatment of trigeminal schwannomas - BAYRAKLI, FATİH (SPRINGER WIEN, 2007)
Background. Trigeminal nerve schwannomas account for 0.07%-0.28% of all intracranial tumours. Advances in skull base surgery have led to more aggressive resection of these tumours, but surgery may associated with development of new neurological deficits. Methods. In this report, we analyse the long-term results 15 patients with newly diagnosed or residual/recurrent trigeminal schwannoma who underwent gamma-knife treatment. Findings. During a mean 61 months of follow-up, MRI revealed reduction of tumour size in 13 and no size change in 2 patients. The tumour growth control rate was 100% and only 1 patient had transient facial numbness and diplopia. Conclusions. For patients with small to moderate size trigeminal schwannomas, gamma-knife radiosurgery is associated with good tumour control and a minimal risk of adverse radiation effects.
Keywords: gamma knife; radiosurgery; schwannoma; trigeminal nerve; STEREOTACTIC RADIOSURGERY; NONACOUSTIC SCHWANNOMAS; ACOUSTIC NEUROMAS; NEURINOMAS; EXPERIENCE; MANAGEMENT; NERVE; THERAPY; SERIES